'Walking the line between saint and sinner': Care and Nurse Jackie. Issue 2 (July 2016) - Gorton, Kristyn
This article considers how the notion of care, whether as an act of kindness or as a moral ethics, is reflected and worked through in the contemporary American television series, Nurse Jackie (2009–2015). Nurse Jackie, a comedy drama set in a fictional Catholic New York City Hospital, explores the 'line between saint and sinner', in the life of an emergency room (ER) nurse. This article considers how Jackie's character negotiates moral boundaries in a way that allows for a reconsideration of both the complexity of care practices in contemporary society and the gendered nature of these practices.